(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
During the latest Argentinean dictatorship (1976-1983), political militant women were persecuted and specially punished in order to their gender. According to dictatorship, they were doubly trangressive: they had made an incursion in politics and they had quitted their traditional roles as women (as mothers, wifes, housewifes, etc.). In concentration camps there was a systematic plan of violence against women, of sexual violence and rape. The intersectonal perspective is an useful implement to analyses the so called recent past in Argentina with a gender perspective, because of the complexity of the experience. This perspective is based on different central concept which refer to inequality, such as sexual orientation, class, age, occupation and profession, religion, disabilities and illness, exile, pregnancy, puerperium, etc. In this article we propose a descriptive approach based on women testimonies (from the book Putas y guerrilleras, by Miriam Lewin and Olga Wornat). They describe the past from sexual violence and rape. We specially follow the ideas of intersectionality by Patricia Hill Collins with Sirma Bilge and María Rodo-Zárate.